A case study of effects from soil-pile interactions to dynamic response of a structure under earthquake - Phongthorn Songdet; Punchet Thammarak; Pennung Warnitchai; Anwar, Naveed; Royal Thai Government Fellowship (Pathum Thani : Asian Institute of Technology, 2013)
The structural analysis of buildings under dynamic excitation has long been studied and developed for decades. The techniques which represent geometrical nonlinearity and inelastic material behavior are available and adopted in the analysis of buildings under extreme events. In other words, state-of-the-art technology is currently exploited to simulate the response of superstructure under dynamic loads. However, a very important component, foundation, is normally neglected and oversimplified. Consequently, this research aims to investigate the effects from foundation modeling to dynamic response of superstructure. Furthermore, the comparison was made between conventional foundation modeling, widely used in nowadays analysis, and proper modeling technique, incorporating soil continuum. This study shows that, in some cases, the response of soil vibration may be amplified and cause the significant increase in building response.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 2013
Keywords: Structural dynamics; Earthquake